Prevalence and determinants of hypertension among adult population in Nepal: Data from Nepal Demographic and Health Survey 2016 - Hasan, Mehedi; Sutradhar, Ipsita; Akter, Tahmina; Gupta, Rajat Das; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2018 Hasan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at : https://doi.org/10.1371/journal.pone.0198028 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0198028